Digital revolution and fake news - Ahmad Farouk, Azeem Fazwan (Sun Media Corporation Sdn. Bhd., 2017)
HE digital revolution and its instantaneous short-term benefits have been celebrated and sold to mankind by peddlers of technology as a blessing in our march towards greater efficiency and productivity. This, it is argued, will fulfil our increasing lust for greater material rewards.